Saptamatrika Panel - Temples of India Project Team (Jio Institute, 2024)
The panel is divided into two sections, displaying the matrikas, each identifiable by their vahanas (mounts) in the following order: Maheshvari, Vaishnavi, Vinadhara Shiva, Varahi, and Kaumari. The section on the left features Aindri (or Indrani) and Chamunda. Shiva, positioned in the centre, holds a veena in his lower two hands and a trident and snake in his upper two hands.